A Simple, Inexpensive Surgical Model for Abdominal Hysterectomy (Out of Print) - David Haas; Gregory Raff (Association of American Medical Colleges, 2008)
Abstract This is an easily constructed model for teaching residents and students the basic techniques involved in clamping, cutting, and suture ligating the uterine artery and pedicle during an abdominal hysterectomy. Several models were constructed and utilized in a surgical curriculum at our residency training program. The residents rated the session highly as an excellent and safe environment to hone and practice the skills utilized during abdominal hysterectomy.